Формулы сокращенного умножения .

Квадрат суммы:

\( (a+b)^2=a^2+2ab+b^2 \)


Квадрат разности:

\( (a-b)^2=a^2-2ab+b^2 \)


Разность квадратов:

\( a^2-b^2=(a-b)(a+b) \)




1.     \((x+y)^2 \)


  

\(x^2+2xy+y^2\)

\( (x+y)^2=x^2+2xy+y^2 \)

ПОЗЖЕ





2.     \((1+y)^2 \)


  

\(1+2y+y^2\)

\( (1+y)^2=1^2+2\cdot1\cdot y+y^2= 1+2y+y^2 \)

ПОЗЖЕ



3.     \((2+y)^2 \)


  

\(4+4y+y^2\)

\( (2+y)^2=2^2+2\cdot2\cdot y+y^2= 4+4y+y^2 \)

ПОЗЖЕ



4.     \((3+y)^2 \)


  

\(9+6y+y^2\)

\( (3+y)^2=3^2+2\cdot3\cdot y+y^2= 9+6y+y^2 \)

ПОЗЖЕ



5.     \((4+y)^2 \)


  

\(16+8y+y^2\)

\( (4+y)^2=4^2+2\cdot4\cdot y+y^2= 16+6y+y^2 \)

ПОЗЖЕ



6.     \((5+y)^2 \)


  

\(25+10y+y^2\)

\( (5+y)^2=5^2+2\cdot5\cdot y+y^2= 25+10y+y^2 \)

ПОЗЖЕ



7.     \((2x+y)^2 \)


  

\(4x^2+4xy+y^2\)

\( (2x+y)^2=(2x)^2+2\cdot2x\cdot y+y^2= 4x^2+4xy+y^2 \)

ПОЗЖЕ



8.     \((3x+y)^2 \)


  

\(9x^2+6xy+y^2\)

\( (3x+y)^2=(3x)^2+2\cdot3x\cdot y+y^2= 9x^2+6xy+y^2 \)

ПОЗЖЕ



9.     \((4x+y)^2 \)


  

\(16x^2+8xy+y^2\)

\( (4x+y)^2=(4x)^2+2\cdot4x\cdot y+y^2= 16x^2+8xy+y^2 \)

ПОЗЖЕ



10.     \((9x+y)^2 \)


  

\(81x^2+18xy+y^2\)

\( (9x+y)^2=(9x)^2+2\cdot9x\cdot y+y^2= 81x^2+18xy+y^2 \)

ПОЗЖЕ



11.     \((15x+y)^2 \)


  

\(225x^2+30xy+y^2\)

\( (15x+y)^2=(15x)^2+2\cdot15x\cdot y+y^2= 225x^2+30xy+y^2 \)

ПОЗЖЕ



12.     \((20x+y)^2 \)


  

\(400x^2+40xy+y^2\)

\( (20x+y)^2=(20x)^2+2\cdot20x\cdot y+y^2= 400x^2+40xy+y^2 \)

ПОЗЖЕ



13.     \( (\dfrac{1}{2}x+y)^2 \)


  

\(\dfrac{1}{4}x^2+xy+y^2\)

\( (\dfrac{1}{2}x+y)^2=(\dfrac{1}{2}x)^2+2\cdot \dfrac{1}{2}x \cdot y+y^2= \dfrac{1}{4}x^2+xy+y^2 \)

ПОЗЖЕ



14.     \( (\dfrac{1}{3}x+y)^2 \)


  

\(\dfrac{1}{9}x^2+\dfrac{2}{3}xy+y^2\)

\( (\dfrac{1}{3}x+y)^2=(\dfrac{1}{3}x)^2+2\cdot \dfrac{1}{3}x \cdot y+y^2= \dfrac{1}{9}x^2+\dfrac{2}{3}xy+y^2 \)

ПОЗЖЕ



15.     \( (\dfrac{1}{4}x+y)^2 \)


  

\(\dfrac{1}{16}x^2+\dfrac{1}{2}xy+y^2\)

\( (\dfrac{1}{4}x+y)^2=(\dfrac{1}{4}x)^2+2\cdot \dfrac{1}{4}x \cdot y+y^2= \dfrac{1}{16}x^2+\dfrac{1}{2}xy+y^2 \)

ПОЗЖЕ



16.     \( (\dfrac{2}{5}x+y)^2 \)


  

\(\dfrac{4}{25}x^2+\dfrac{4}{5}xy+y^2\)

\( (\dfrac{2}{5}x+y)^2=(\dfrac{2}{5}x)^2+2\cdot \dfrac{2}{5}x \cdot y+y^2= \dfrac{4}{25}x^2+\dfrac{4}{5}xy+y^2 \)

ПОЗЖЕ



17.     \( (\dfrac{9}{2}x+y)^2 \)


  

\(\dfrac{81}{4}x^2+9xy+y^2\)

\( (\dfrac{9}{2}x+y)^2=(\dfrac{9}{2}x)^2+2\cdot \dfrac{9}{2}x \cdot y+y^2= \dfrac{81}{4}x^2+9xy+y^2 \)

ПОЗЖЕ



18.     \( (ax+by)^2 \)


  

\(a^2x^2+2axby+b^2y^2\)

\( (ax+by)^2=(ax)^2+2\cdot ax \cdot by+(by)^2= a^2x^2+2axby+b^2y^2 \)

ПОЗЖЕ



19.     \( (ax+bx)^2 \)


  

\(a^2x^2+2ax^2b+b^2x^2 \)

\( (ax+bx)^2=(ax)^2+2\cdot ax \cdot bx+(bx)^2= a^2x^2+2ax^2b+b^2x^2 \)

ПОЗЖЕ



20.     \( (3x+5y)^2-30xy \)


  

\(9x^2+25y^2 \)

\( (3x+5y)^2-30xy=(3x)^2+2\cdot 3x \cdot 5y+(5y)^2-30xy= \)
\( = 9x^2+30xy+25y^2-30xy= 9x^2+25y^2 \)

ПОЗЖЕ



21.     \( (4x+6y)^2-16x^2-36y^2 \)


  

\(48xy \)

\( (4x+6y)^2-16x^2-36y^2=(4x)^2+2\cdot 4x \cdot 6y+(6y)^2-16x^2-36y^2= \)
\( = 16x^2+48xy+36y^2-16x^2-36y^2= 48xy \)

ПОЗЖЕ



22.     \( (4x+6y)^2-16x^2-36y^2 \)


  

\(48xy \)

\( (4x+6y)^2-16x^2-36y^2=(4x)^2+2\cdot 4x \cdot 6y+(6y)^2-16x^2-36y^2= \)
\( = 16x^2+48xy+36y^2-16x^2-36y^2= 48xy \)

ПОЗЖЕ



23.     \( (x-y)^2 \)


  

\(x^2-2xy+y^2 \)

\( (x-y)^2=x^2-2\cdot x \cdot y+y^2= x^2-2xy+y^2 \)

ПОЗЖЕ



24.     \( (1-y)^2 \)


  

\(1-2y+y^2 \)

\( (1-y)^2=1^2-2\cdot 1 \cdot y+y^2= 1-2y+y^2 \)

ПОЗЖЕ



25.     \( (2-y)^2 \)


  

\(4-4y+y^2 \)

\( (2-y)^2=2^2-2\cdot 2 \cdot y+y^2= 4-4y+y^2 \)

ПОЗЖЕ



26.     \( (3-y)^2 \)


  

\(9-6y+y^2 \)

\( (3-y)^2=3^2-2\cdot 3 \cdot y+y^2= 9-6y+y^2 \)

ПОЗЖЕ



27.     \( (4-y)^2 \)


  

\(16-8y+y^2 \)

\( (4-y)^2=4^2-2\cdot 4 \cdot y+y^2= 16-8y+y^2 \)

ПОЗЖЕ



28.     \( (5-y)^2 \)


  

\(25-10y+y^2 \)

\( (5-y)^2=5^2-2\cdot 5 \cdot y+y^2= 25-10y+y^2 \)

ПОЗЖЕ



29.     \( (30-y)^2 \)


  

\(900-60y+y^2 \)

\( (30-y)^2=30^2-2\cdot 30 \cdot y+y^2= 900-60y+y^2 \)

ПОЗЖЕ



30.     \( (2x-y)^2 \)


  

\(4x^2-4xy+y^2 \)

\( (2x-y)^2=(2x)^2-2\cdot 2x \cdot y+y^2= 4x^2-4xy+y^2 \)

ПОЗЖЕ



31.     \( (3x-y)^2 \)


  

\(9x^2-6xy+y^2 \)

\( (3x-y)^2=(3x)^2-2\cdot 3x \cdot y+y^2= 9x^2-6xy+y^2 \)

ПОЗЖЕ



32.     \( (4x-y)^2 \)


  

\(16x^2-8xy+y^2 \)

\( (4x-y)^2=(4x)^2-2\cdot 4x \cdot y+y^2= 16x^2-8xy+y^2 \)

ПОЗЖЕ



33.     \( (5x-y)^2 \)


  

\(25x^2-10xy+y^2 \)

\( (5x-y)^2=(5x)^2-2\cdot 5x \cdot y+y^2= 25x^2-10xy+y^2 \)

ПОЗЖЕ



34.     \( (\dfrac{1}{3}x-y)^2 \)


  

\(\dfrac{1}{9}x^2-\dfrac{2}{3}xy+y^2 \)

\( (\dfrac{1}{3}x-y)^2=(\dfrac{1}{3}x)^2-2\cdot \dfrac{1}{3}x \cdot y+y^2= \dfrac{1}{9}x^2-\dfrac{2}{3}xy+y^2 \)

ПОЗЖЕ



35.     \( (\dfrac{1}{2}x-y)^2 \)


  

\( \dfrac{1}{4}x^2-xy+y^2 \)

\( (\dfrac{1}{2}x-y)^2=(\dfrac{1}{2}x)^2-2\cdot \dfrac{1}{2}x \cdot y+y^2= \dfrac{1}{4}x^2-xy+y^2 \)

ПОЗЖЕ



36.     \( (\dfrac{3}{8}x-y)^2 \)


  

\( \dfrac{9}{64}x^2-\dfrac{3}{4}xy+y^2 \)

\( (\dfrac{3}{8}x-y)^2=(\dfrac{3}{8}x)^2-2\cdot \dfrac{3}{8}x \cdot y+y^2= \dfrac{9}{64}x^2-\dfrac{3}{4}xy+y^2 \)

ПОЗЖЕ



37.     \( (x-y)^2+(x+y)^2 \)


  

\( 2x^2+2y^2 \)

  

или

  

\( 2(x^2+y^2) \)

\( (x-y)^2+(x+y)^2=x^2-2xy+y^2+x^2+2xy+y^2=2x^2+2y^2 \)

ПОЗЖЕ



38.     \( (x-y)^2-(x+y)^2 \)


  

\( -4xy \)

\( (x-y)^2-(x+y)^2=x^2-2xy+y^2-x^2-2xy-y^2=-4xy \)

ПОЗЖЕ



39.     \( (3x-y)^2-(3x+y)^2 \)


  

\( -12xy \)

\( (3x-y)^2-(3x+y)^2=9x^2-6xy+y^2-9x^2-6xy-y^2=-12xy \)

ПОЗЖЕ



40.     \( (5x-y)^2-(x-5y)^2 \)


  

\( 24x^2-24y^2 \)


или
  

\( 24(x^2-y^2) \)

\( (5x-y)^2-(x-5y)^2=25x^2-10xy+y^2-(x^2-10xy+25y^2)= \)

\( 25x^2-10xy+y^2-x^2+10xy-25y^2=24x^2-24y^2 \)

ПОЗЖЕ



41.     \( (2x-2y)^2-4(x-y)^2 \)


  

\( 0 \)

\( (2x-2y)^2-4(x-y)^2=4x^2-8xy+4y^2-4(x^2-2xy+y^2)= \)

\( 4x^2-8xy+4y^2-4x^2+8xy-4y^2=0 \)

ПОЗЖЕ



42.     \( (3x-2y)^2-6(x-y)^2 \)


  

\( 3x^2-2y^2 \)

\( (3x-2y)^2-6(x-y)^2=9x^2-12xy+4y^2-6(x^2-2xy+y^2)= \)

\( 9x^2-12xy+4y^2-6x^2+12xy-6y^2=3x^2-2y^2 \)

ПОЗЖЕ



43.     \( \dfrac{x^2-y^2}{x-y} \)


  

\( x+y \)

\( \dfrac{x^2-y^2}{x-y}=\dfrac{(x-y)(x+y)}{x-y}=\dfrac{(x+y)}{1}=x+y \)

ПОЗЖЕ



44.     \( \dfrac{x^2-y^2}{x+y} \)


  

\( x-y \)

\( \dfrac{x^2-y^2}{x+y}=\dfrac{(x-y)(x+y)}{x+y}=\dfrac{(x-y)}{1}=x-y \)

ПОЗЖЕ



45.     \( \dfrac{4x^2-9y^2}{2x+3y} \)


  

\( 2x-3y \)

\( \dfrac{4x^2-9y^2}{2x+3y}=\dfrac{(2x-3y)(2x+3y)}{2x+3y}=\dfrac{(2x-3y)}{1}=2x-3y \)

ПОЗЖЕ



46.     \( \dfrac{9x^2-16y^2}{3x+4y} \)


  

\( 3x-4y \)

\( \dfrac{9x^2-16y^2}{3x+4y}=\dfrac{(3x-4y)(3x+4y)}{3x+4y}=\dfrac{(3x-4y)}{1}=3x-4y \)

ПОЗЖЕ